Blues music in the sixties : a story in Black and White - Adelt, Ulrich, 1972- (Rutgers University Press, 2010)
In the 1960s, within the larger context of the civil rights movement and the burgeoning counterculture, the blues changed from black to white in its production and reception, as audiences became increasingly white. Yet, while this was happening, blackness-especially black masculinity-remained a marker of authenticity. Blues Music in the Sixties discusses these developments, including the international aspects of the blues. It highlights the performers and venues that represented changing racial politics and addresses the impact and involvement of audiences and cultural brokers.